The Neural Correlates of the Abnormal Implicit Self-Esteem in Major Depressive Disorder: An Event-Related Potential Study - Jiang, Chen-guang; Lu, Heng; Zhang, Jia-zhao; Gao, Xue-zheng; Wang, Jun; Zhou, Zhen-he (Frontiers in Psychiatry, 2022)
Implicit self-esteem (ISE) has been considered a critical factor in the development and maintenance of major depressive disorder (MDD). Further investigating the event-related potential (ERP) characteristics underlying abnormal ISE in MDD would be helpful for understanding the neural mechanism of MDD. For this purpose, 32 MDD patients and 31 age- and sex-matched healthy controls (HCs) were enrolled in this study. The Rosenberg Self-Esteem Scale (RSES) was used to evaluate explicit self-esteem (ESE), and a self-esteem go/no-go association task (GNAT) was used to assess ISE. Electroencephalograms were synchronously recorded when performing the self-esteem GNAT. Behavioral data and ERP characteristics under different conditions were analyzed and compared within and across groups. The results showed that compared to HCs, MDD patients had significantly lower RSES scores and self-D scores of GNAT, which reflected lower levels of ESE and ISE, respectively. No significant correlation was found between RESE and self-D scores, and only RESE scores were significantly negatively correlated with the Hamilton Depression Rating Scale (HAMD) score. The averaged centroparietal go-P3 amplitude under the self-positive condition was significantly smaller in MDD than in HCs. Moreover, HCs had a significantly larger average centroparietal go-P3 amplitude in self-positive than in self-negative conditions, while this pattern was opposite in the MDD group. The neural activity patterns for other conditions were similar between MDD and HCs. Our results suggested that patients with MDD have a decreased level of both ESE and ISE, and ISE might be more independent of clinical symptoms. Decreased neural processing that implicitly associate self with positive conditions (and relatively increased implicit association between self and negative conditions) might be important neural correlates for abnormal ISE in MDD.